2D and 3D TCAD simulation of III-V channel FETs at the end of scaling. (September 2019) - Aguirre, P.; Rau, M.; Schenk, A.
Abstract: Quantum drift diffusion corrections, models for the one- and two-dimensional density of states, a non-local model for source-to-drain tunneling, and a simple ballistic mobility model are jointly used to simulate I D V GS -characteristics of scaled III-V-channel nFETs. The sub-threshold swing of double-gate ultra-thin-body and gate-all-around nanowire geometries are extracted for different gate lengths, and the semi-classical results are compared with those from the quantum transport simulator QTx. The low-dimensional density of states in combination with the ballistic mobility yields an overall good agreement with the QTx transfer curves after the onset of inversion and decreases I ON by two orders of magnitude in comparison to the simulation with a large diffusive mobility. It is shown that source-to-drain tunneling sets a limit to scaling at a gate length of about 10 nm due to the degradation of the sub-threshold swing. Simulating this effect with a low-dimensional density of states reveals inconsistencies. They are attributed to the tunneling model, which had been derived for a three-dimensional electron gas.